2021
DOI: 10.3390/ijms22105366
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles from Plants: Current Knowledge and Open Questions

Abstract: The scientific interest in the beneficial properties of natural substances has been recognized for decades, as well as the growing attention in extracellular vesicles (EVs) released by different organisms, in particular from animal cells. However, there is increasing interest in the isolation and biological and functional characterization of these lipoproteic structures in the plant kingdom. Similar to animal vesicles, these plant-derived extracellular vesicles (PDEVs) exhibit a complex content of small RNAs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 75 publications
(162 reference statements)
4
77
0
Order By: Relevance
“…That of LEVs-TMO stored at 45 °C was changed to negative charge at 4w (Figure S5d) Zeta potentials may have functional consequences for the EVs, such as by inducing alterations in aggregation, protein structures, surface modifications, and/or protein unfolding/denaturation. As Maroto et al reported that freezing of exosomes can diminish their zeta potential [40], we found that the surface charge of LEVs-TMO was slightly decreased at −20 °C. To examine quantity change during storage, we measured the total protein level under different temperatures and increasing storage time.…”
Section: Physiological Properties Of Levs Lev-13-bg and Levs-tmo Over...supporting
confidence: 55%
See 1 more Smart Citation
“…That of LEVs-TMO stored at 45 °C was changed to negative charge at 4w (Figure S5d) Zeta potentials may have functional consequences for the EVs, such as by inducing alterations in aggregation, protein structures, surface modifications, and/or protein unfolding/denaturation. As Maroto et al reported that freezing of exosomes can diminish their zeta potential [40], we found that the surface charge of LEVs-TMO was slightly decreased at −20 °C. To examine quantity change during storage, we measured the total protein level under different temperatures and increasing storage time.…”
Section: Physiological Properties Of Levs Lev-13-bg and Levs-tmo Over...supporting
confidence: 55%
“…We collected fresh leaves of Dendropanax morbifera from Bogil Island, which is located in Wando-gun, Jeollanam-do, South Korea. Unlike the general method for isolating plant vesicles [39][40][41], we have developed a method for isolating EVs from Dendropanax morbifera leaf to facilitate industrial application. Dendropanax morbifera-derived EVs were isolated by processing the leaves with a mixer grinder plus extractor, passing the resulting crude leaf extract through filter paper, and centrifuging the obtained extract at 10,000× g for 10 min.…”
Section: Isolation Of D Morbifera Leaf-derived Extracellular Vesiclesmentioning
confidence: 99%
“…In the last few years, a growing interest was focused on the discovery of nanovesicles from edible plants, such as fruits and vegetables ( 19 , 28 , 29 ). The deep characterization of these vesicles revealed the presence of bioactive molecules (i.e., nucleic acids, proteins, lipids, and small RNAs), just like the mammalian exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…The high heterogeneity of plant-derived EVs population and lack of specific markers make their characterization a challenge. Comprehensive omics analysis might help to identify potential characteristics and molecular profiles of EVs from different species [ 222 ]. Furthermore, future protocols with certain stimuli for specific plants species might be developed to produce naturally derived EVs containing qualities of interest, such as wound healing properties.…”
Section: Future Perspectivesmentioning
confidence: 99%